The Greening of the Automotive Industry - Calabrese, G.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
An examination of the greening of the automotive industry by the path dependence of countries and carmakers' trajectories. Three sources of path dependency can be detected: business models, consumer attitudes, and policy regulations. The automobile is changing and the race towards alternative driving systems has started!
Keywords: Industrial management—Environmental aspects; International business enterprises; Transportation; Management; Industrial management; Industries; Sustainability Management; International Business; Transportation; Innovation/Technology Management; Corporate Environmental Management; Industries